L’ouverture au marché en Chine (années 1980-2000) et le développement économique local : une forme de gouvernance multi-niveaux ? - Liao Liao; Jean-Pierre Gaudin (Cybergeo, 2017)
China has been considered a centralized country for a long period of time. With several reforms over the last 30 years, important powers in economic development have been gradually transferred to local levels. The article analyzes this evolution based on a field study in two provinces, Zhejiang and Sichuan. The hypothesis is that the transfer of initiatives becomes a new mode of steering the local development in China. The analysis presented in this article is based on two perspectives: one perspective is  about the financial, administrative, and political reform in China; the other perspective is to examine the role of local actors in territorial development and the intergovernmental relations within the provinces.